2015
DOI: 10.1002/sce.21152
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Use of Evidence in Argumentation Through Practice in Argumentation and Reflection in the Context of SOCRATES Learning Environment

Abstract: The aim of this study was to examine how students used evidence in argumentation while they engaged in argumentive and reflective activities in the context of a designed learning environment. A web-based learning environment, SOCRATES, was developed, which included a rich data base on the topic of Climate Change. Sixteen 11 th graders, working with a partner, engaged in electronic argumentive dialogs with classmates who held an opposing view on the topic and in some evidence-focused reflective activities, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 44 publications
5
67
0
7
Order By: Relevance
“…Subjective epistemic standards, such as agreement with one's own knowledge, are predominant in adolescents' judgments about the trustworthiness of sources (Mason, Boldrin, & Ariasi, 2010) and about the veracity of knowledge claims (Mason, Ariasi, & Boldrin, 2011). Iordanou and Constantinou (2015) examined how 15-and 16-year-olds argue with peers who hold opposing views on a socio-scientific issue, in a knowledge-rich learning environment. Participants' dialogue transcripts were analyzed in terms of the overall use of evidence, the amount of evidence per argument and per counterargument, the function of evidence use and the accuracy of the evidence employed.…”
Section: Epistemic Standards In Adolescencementioning
confidence: 99%
See 1 more Smart Citation
“…Subjective epistemic standards, such as agreement with one's own knowledge, are predominant in adolescents' judgments about the trustworthiness of sources (Mason, Boldrin, & Ariasi, 2010) and about the veracity of knowledge claims (Mason, Ariasi, & Boldrin, 2011). Iordanou and Constantinou (2015) examined how 15-and 16-year-olds argue with peers who hold opposing views on a socio-scientific issue, in a knowledge-rich learning environment. Participants' dialogue transcripts were analyzed in terms of the overall use of evidence, the amount of evidence per argument and per counterargument, the function of evidence use and the accuracy of the evidence employed.…”
Section: Epistemic Standards In Adolescencementioning
confidence: 99%
“…Studying students engaging in dialogic argumentation over time offers insights regarding how both knowledge and epistemic cognition change. Iordanou and Constantinou (2015), employing the micro-genetic method, a powerful method for understanding epistemic cognitive development (Sandoval, 2014), examined how students use evidence to influence the beliefs of their peers. Eleventh graders, working with a partner, engaged in electronic argumentative dialogues with classmates who held an opposing view on the topic and in some evidence-focused reflective activities, based on transcriptions of their dialogues.…”
Section: Understanding Of Epistemic Standards and Control Of Their Apmentioning
confidence: 99%
“…Our dialogic method has been successful in enhancing students' argumentative writing (Hemberger, Kuhn, Matos, & Shi, 2017;Kuhn & Crowell, 2011;Kuhn, Hemberger, & Khait, 2016a) -widely regarded as a key educational objective and modality for display of critical thinking -as well as dialogic skills themselves (Crowell & Kuhn, 2014;Iordanou & Constantinou, 2015;Kuhn & Moore, 2015) and the disposition to use them (Kuhn & Zillmer, 2015). What accounts for its success, especially in the domain of argumentative writing, where students of all ages have long been reported to perform poorly (Newell, Beach, Smith, & VanDerHeide, 2011)?…”
Section: Evolution Of Argument In Discourse and Writing Over The Courmentioning
confidence: 99%
“…Many researchers have emphasized the importance of evaluating evidence and explanations in enhancing the quality of argumentation (Iordanou & Constantinou, 2015;Kenyon & Reiser, 2006;Maloney & Simon, 2006;Osborne et al, 2004;Sampson, Grooms, & Walker, 2011). For example, Kenyon and Reiser (2006) observed that offering students the criteria needed to evaluate evidence and explanations can help them produce better work.…”
Section: Evaluating Evidence and Explanationsmentioning
confidence: 97%